Adaptation co-benefits of solar irrigation: evidence from Bangladesh - Buisson, Marie-Charlotte; Mitra, Archisman; Hounsa, T.; Habib, A.; Mukherji, Aditi (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2022)
The mitigation benefits of solar irrigation pumps (SIPs), when those SIPs replace diesel pumps, are well understood. What is not equally known are the adaptation co-benefits of SIPs. This brief evaluates the co-benefits of using SIPs instead of widely used diesel pumps for farmers in Bangladesh. It estimates the impact of access to SIP on household and crop levels outcomes for improving farmer livelihoods and food security. In doing so, it explores the potential pathways of these impacts.